THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE AND PERCEPTION OF THE USE OF TRADITIONAL MEDICINE IN THE PEOPLE OF KLATEN CITY IN 2022 - Tista Ayu Fortuna; Arifah Sri Wahyuni; Nadya Tiara Putri (Universitas Muhammadiyah Magelang, 2023)
The use of traditional medicine in today's society is increasing with labels